2008
DOI: 10.1016/j.cognition.2007.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Scale structure: Processing minimum standard and maximum standard scalar adjectives

Abstract: Gradable adjectives denote a function that takes an object and returns a measure of the degree to which the object possesses some gradable property (Kennedy, 1999). Scales, ordered sets of degrees, have begun to be studied systematically in semantics (Kennedy, to appear, Kennedy & McNally, 2005, Rotstein & Winter, 2004. We report four experiments designed to investigate the processing of absolute adjectives with a maximum standard (e.g., clean) and their minimum standard antonyms (dirty). The central hypothes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 24 publications
1
21
0
1
Order By: Relevance
“…Frazier et al (2008) have shown that this default reference point is involved in the on-line processing of sentences containing absolute adjectives. However, in some contexts this default reference point may be overridden by another reference point, as in (12) and (13): (12) The restaurant is very full tonight.…”
Section: A Unified Approach: Construals With Multiple Reference Pointsmentioning
confidence: 99%
“…Frazier et al (2008) have shown that this default reference point is involved in the on-line processing of sentences containing absolute adjectives. However, in some contexts this default reference point may be overridden by another reference point, as in (12) and (13): (12) The restaurant is very full tonight.…”
Section: A Unified Approach: Construals With Multiple Reference Pointsmentioning
confidence: 99%
“…(19) Total-partial adjectives : dry-moist, clean-dirty, healthy-sick, straightbent/curved, smooth-rough, complete-incomplete, sharp-unsharp/blurred The distinction between total and partial adjectives was recently corroborated by (Frazier et al 2006) Rotstein and Winter (henceforth R&W) point out that with some total-partial pairs of adjectives this contrast in acceptability is not so sharp. For instance, according to our intuitive criterion, the adjectives healthy and sick should be classified as a total-partial pair, but almost sick is not worse than almost healthy.…”
Section: 'Almost' and The Total/partial Distinctionmentioning
confidence: 80%
“…Conceiving scales as abstract spatial representations has rarely been done explicitly yet (but compare the vector-based approaches in Winter 2005 andFlieger 2009). Assuming cognitive reality of scales with associated spatial properties is in line with Clark et al (1973) or Frazier et al (2008) whose results suggest that "semantically introduced scales are part of the obligatory computation of the meaning of the sentence" (Frazier et al 2008: 31). Such a view is also corroborated by the fact that degree relations can be expressed with spatial relation terms, as in He is over/under 10 feet tall (cf.…”
Section: Degrees and Explicit Degree Relationsmentioning
confidence: 95%